Genomic Perspectives on Aeromonas salmonicida subsp. salmonicida Strain 890054 as a Model System for Pathogenicity Studies and Mitigation of Fish Infections - Gauthier, Jeff; Marquis, Hélène; Paquet, Valérie E.; Charette, Steve J.; Levesque, Roger C.; Derome, Nicolas (Frontiers in Marine Science, 2021)
Aeromonas salmonicida subsp. salmonicida is a Gram-negative bacterium that causes furunculosis, a fish disease claiming substantial economic losses in the aquaculture industry. Major challenges exist in monitoring and controlling fish infections in aquaculture farms. Development of management practices to improve the sustainability of fish farming with disease prevention necessitates studies using well-defined systems and well-characterized bacterial isolates. Even though several A. salmonicida subsp. salmonicida genomes have been completely assembled and thoroughly annotated, in vivo pathogenicity data are lacking. Here we present A. salmonicida subsp. salmonicida 890054 as a prototype strain for standardized furunculosis challenges with survival data. Computational analysis of sequencing results provided a complete circular genome with annotations of plasmids carrying virulence factors, antimicrobial resistance, and secondary metabolite coding genes. The analysis also revealed the presence of an IncU plasmid distinct from other IncU plasmids previously associated with Aeromonas.